Adverse effects of non-biodegradable and compostable plastic bags on the establishment of coastal dune vegetation: First experimental evidences. (September 2019) - Menicagli, Virginia; Balestri, Elena; Vallerini, Flavia; Castelli, Alberto; Lardicci, Claudio
Graphical abstract: Image 1 Highlights: Shopping bags are a consistent fraction of plastic litter deposited in beaches. Effects of beached bags on dune plant recruitment from seed have been neglected. Non-biodegradable and compostable bags reduced the emergence of three dune plants. Bags differentially affected seedling growth and morphology of the study species. Bag effects could translate in changes in plant communities and dune structure. Abstract : Non-biodegradable and compostable plastic bags on beaches negatively affect the development of coastal dune vegetation by drastically reducing seedling emergence and growth.